V.I. Lenin making a speech at the unveiling of a memorial to K. Marx and F. Engels in Voskresenskaya Square (now Revolution Square) in Moscow. Compare: 69/39 A, page 96
V.I. Lenin making a speech at the unveiling of a memorial to K. Marx and F. Engels in Voskresenskaya Square (now Revolution Square) in Moscow. Compare: 69/39 A, page 96.